(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Yuvana Pidaka (Acne Vulgaris) is a most common complaint experienced during adolescence and is regarded as swabhavaja (natural phenomenon). It is an annoying problem seen in both genders during adolescence which can even decrease one’s self-esteem and confidence. In Ayurveda Yuvana Pidaka is described under Ksudra rogas, which is caused due to vitiation of Kapha, Vata doshas and Rakta dushti. It is considered as Sukra dhatu mala by Acarya Sarangadhara. If this problem is not addressed properly these Pidakas may become chronic and can leave permanent scars. So, better understanding of the Nidana, Lakshanas and Samprapthi of disease helps the physician to opt for accurate treatment. This article emphasizes on the literature available for this disease in classics and establishes a clear understanding of the Nidana Panchaka. All the formulations described in this article are from various Ayurvedic classics which were time tested and prove their efficacy even in this present era and are safe and economic.